PENERAPAN METODE MAGIC MEMORY AL-QURAN UNTUK MENINGKATKAN HAFALAN SISWA PADA MATA PELAJARAN AL-QURAN HADITS DI KELAS VIII MTS PONDOK PESANTREN MODERN AL-FADHLAH KECAMATAN MINAS KABUPATEN SIAK - Khairun Nur; Bustanur Bustanur; Helbi Akbar (Universitas Islam Kuantan Singingi, 2022)
The Tahfidz Qur'an program is a very noble activity and is loved by Allah SWT, the Tahfidz Qur'an Program is also a training of thought and memory. Erwin Kurnia Wijaya revealed a method of memorizing the Qur'an known as the Al-Quran Magic Memory Method. However, the fact that the author found at the Al-Fadhlah Modern Islamic Boarding School is not fully the role of the Al-Quran Magic Memory Method, the evidence is that there are still students and female students who have difficulty memorizing the Qur'an. This study aims to determine how the Al-Quran Magic Memory Method improves students' memorization. This type of research is Field Action Research, with data collection techniques are Interview, Documentation, and Observation. After analyzing it, it can be concluded that the role of the Al-Quran Magic Memory Method in improving memorization has a good effect and has a strong enough portion in shaping memorization. Judging from the entire Qur'an memorization activity, it has covered the entire process of applying the Magic Memory Method, namely memorizing letter identities, memorizing verse sounds based on remembering style, memorizing the sounds of the initial verse with verse numbers, muraja'ah (repeating) memorization per page with the AMMA pattern ( Start-Forward-Backward-Random).